2000
DOI: 10.1667/0033-7587(2000)153[0093:iombti]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Malignant Bone Tumors in Radium-224 Patients: Risk Estimates Based on the Improved Dosimetry

Abstract: Mainly between 1945 and 1955, several thousand German patients with ankylosing spondylitis, tuberculosis, or--in a few cases--other diseases received multiple injections of the short-lived alpha-particle emitter radium-224. In the early 1950s, the follow-up of 899 patients was initiated, and the study has continued since then. It includes most of the high-dose patients and nearly all of those treated as children or juveniles, i.e. under the age of 21. In the study cohort, 56 malignant bone tumors occurred in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…From about 1940 to 1980, several thousand German patients with noncancerous diseases have received 224 Ra against ankylosing spondylitis or bone tuberculosis (35,36). 224 …”
Section: Discussionmentioning
confidence: 99%
“…From about 1940 to 1980, several thousand German patients with noncancerous diseases have received 224 Ra against ankylosing spondylitis or bone tuberculosis (35,36). 224 …”
Section: Discussionmentioning
confidence: 99%
“…However, at intermediate dose levels (below 20 Gy to the bone for 226 Ra), no significant increase in cancer was observed in humans (56). For several decades, injections of 224 Ra (t 1/2 = 3.2 days) were used to treat ankylosing spondylitis (56,57). Radium-224 was recently reintroduced and reapproved for ankylosing spondylitis in Germany (41).…”
Section: Discussionmentioning
confidence: 99%
“…Radium-224 was recently reintroduced and reapproved for ankylosing spondylitis in Germany (41). For 224 Ra, long-term follow-up of patients receiving moderate levels revealed no significant difference in overall cancer incidence or life expectancy compared with a control population (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The risk of OS has been reported to be increased following the internal exposure to bone-seeking radioisotopes from occupational or medicinal use. [6][7][8] Interestingly, some studies have revealed the genetic and cytogenetic changes in radiation-induced OS and suggested the presence of additional tumor-associated genes. [9][10][11] However, the changes in global gene expression in radiation-induced OS remain unknown.…”
Section: Uiccmentioning
confidence: 99%